Weed interference on productivity of bell pepper crops - Uljol, L. H.O. [UNESP]; Bianco, S. [UNESP]; Filho, A. B.C. [UNESP]; Bianco, M. S.; Carvalho, L. B. [UNESP] (My University, 2018)
The objective of this work was to determine the interference periods of weeds of the bell pepper cultivar ‘Dahra’. Two experiments were conducted during the years 2014/15 (harvest with lower rainfall) and 2015/16 (harvest with higher rainfall). The treatments consisted of 11 growing periods of cohabitation and weed control with ‘Dahra’ bell peppers: 14, 28, 42, 56, 70, 84, 98, 112, 126, 140 and 154 days after transplanting (DAT). For the determination of the interference periods, the productivity data were analyze using the Boltzmann sigmoidal regression model. The main weeds were Eleusine indica, Brachiaria plantaginea, Digitaria nuda and Nicandra physaloides for presenting high biomass and relative density. The concomitance of these weeds caused losses of up to 85.22% (2014/15) and 86.2% (2015/16) in the fruit yield. It was found that, respectively, for the years 2014/15 and 2015/16, the period before the interference was 17 and 11 DAT, and the total interference prevention period of 71 and 89 DAT. Considering a tolerance of 5% in reducing bell pepper yield, it is recommended that weed control be performed from 11 to 89 DAT.
Interferência de plantas daninhas na produtividade do pimentão
Keywords: Capsicum annuum; Coexistence; Competition